6
$\begingroup$

In Quantum Optics and Quantum Mechanics, the time evolution operator

$$U(t,t_i) = \exp\left[\frac{-i}{\hbar}H(t-t_i)\right]$$

is used quite a lot.

Suppose $t_i =0$ for simplicity, and say the eigenvalue and eigenvectors of the hamiltionian are $\lambda_i, \left|\lambda_i\right>$. Now, nearly every book i have read and in my lecture courses the following result is given with very little or no explanation:

$$U(t,0) = \sum\limits_i \exp\left[-\frac{i}{\hbar}\lambda_it\right]\left|\lambda_i\right>\left<\lambda_i\right|$$

This is quite a logical jump and I can't see where it comes from, could anyone enlighten me?

$\endgroup$

2 Answers 2

7
$\begingroup$

Starting with:

$$U(t,t_i) = e^{\frac{-i}{\hbar }H(t-t_i)}$$

If $t_i=0$:

$$U(t,0) = e^{\frac{-i}{\hbar }Ht}$$

Using the identity: $\sum\limits_i \left|\lambda_i\right>\left<\lambda_i\right|=\mathbb{I}$

$$U(t,0) = \sum\limits_i e^{\frac{-i}{\hbar }Ht}\left|\lambda_i\right>\left<\lambda_i\right|$$

Since the exponential of an operator is (by Taylor expanding): $e^H=\mathbb{I}+H+\frac{1}{2}H^2+\dots$

And: $H\left| \lambda_i \right> =\lambda_i \left| \lambda_i \right>$

You should be able to see that:

$$U(t,0) = \sum\limits_i e^{\frac{-i}{\hbar }\lambda_it}\left|\lambda_i\right>\left<\lambda_i\right|$$

$\endgroup$
1
  • $\begingroup$ I always forget about the series expansion, thanks very much $\endgroup$
    – StickyCube
    Commented May 18, 2013 at 17:06
2
$\begingroup$

Without loss of generality, let's take the $|\lambda_i\rangle$ to be orthonormal. Notice that, by the spectral theorem, the hamiltonian can be written as follows: $$ H = \sum_i \lambda_i P_i, \qquad P_i = |\lambda_i\rangle\langle \lambda_i| $$ Each operator $P_i$ is a projectors onto the subspace spanned by $|\lambda_i\rangle$. Notice, in particular, that $$ P_i^2 = P_i, \qquad P_iP_j = P_jP_i = 0 $$ and a mathematical induction argument gives $$ P_i^n = P_i $$ for all $n\geq 1$. Now, for notational simplicity let $$ \mu = -\frac{i}{\hbar}t $$ Then we have $$ U(t,0) = e^{\mu H} = \sum_{n=0}^\infty \frac{1}{n!}\mu^nH^n $$ but notice that using the properties of projection operators written above, we have $$ H^n = \sum_{i_1, \dots, i_n}\lambda_{i_1}\cdots\lambda_{i_n}P_{i_1}\cdots P_{i_n} = \sum_i\lambda_i^nP_i $$ and therefore $$ U(t,0) = \sum_i\sum_n\frac{1}{n!}(\mu\lambda_i)^nP_i = \sum_ie^{\mu\lambda_i}P_i $$ as desired.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.